Merry Christmas from the Very Hungry Caterpillar - Carle, Eric (Grosset & Dunlap, an imprint of Penguin Random House, 2017)
The Very Hungry Caterpillar celebrates the holiday season, from presents and snowflakes to Santa Claus.